Analisis Ketercapaian Pembelajaran Berdiferensiasi pada Siswa Kelas XII SMA Bangkinang Kabupaten Kampar - Ivo Apristi (PT PUSTAKA CENDEKIA GROUP, 2024)
Education plays an important role in shaping the future of a nation, so that educational reforms continue to be carried out to improve its quality. One of the latest policies in the Indonesian education system is the implementation of the Independent Curriculum, which aims to create more relevant, contextual, and inclusive learning. However, the implementation of this curriculum faces various challenges, especially in the implementation of differentiated learning at the Senior High School (SMA) level. This study aims to analyze the implementation of differentiated learning in the Independent Curriculum in Senior High Schools in Bangkinang, Kampar Regency. This study uses a qualitative approach with a case study method, where data is collected through semi-structured interviews with teachers. Data analysis was carried out by following the five-phase cycle of Yin (2011), namely compiling, dismantling, assembling, interpreting, and concluding. The results of the study show that the implementation of differentiated learning still faces various obstacles, such as limited teacher technology skills, low student interest in learning, and monotonous classroom conditions. However, there are opportunities to improve the effectiveness of learning through teacher training, utilization of technology, and more interesting and varied learning strategies. The conclusion of this study confirms that although differentiated learning in the Independent Curriculum still faces various challenges, efforts to improve teacher skills and more innovative learning strategies can help optimize its implementation. Recommendations from this study are expected to be input for schools and policy makers in improving the quality of education in Indonesia.